Analysis of Budget Solvency in Regencies/Cities of West Nusa Tenggara Province 2019–2023 - Hidayanti, Septiana Rizkika; Sriningsih, Siti; Wafik, Ahmad Zaenal (Economy and Finance Enthusiastic, 2025)
Budget solvency is a critical indicator of a local government's ability to meet its financial obligations and sustain essential public services over time. In the context of increasing demands for fiscal accountability and regional autonomy, assessing the financial health of local governments has become increasingly urgent, particularly in regions with diverse economic capacities such as West Nusa Tenggara Province. This study aims to analyze the budget solvency of municipal and regency governments in West Nusa Tenggara Province from 2019 to 2023. The research employs a descriptive quantitative approach. The data used in this study are secondary data from the Budget Realization Reports of regency and municipal governments in West Nusa Tenggara Province for the 2019–2023 period. Budget solvency is assessed through a three-stage calculation: (1) computing four solvency ratios related to revenue and expenditure; (2) standardizing these ratios into index values using normalization; and (3) averaging the index values to obtain the budget solvency dimension index. Budget solvency analysis is conducted using calculations of the budget solvency ratio, the budget solvency ratio index, and the budget solvency dimension index, which serve as the final measures of budget solvency. Based on the analysis results, it was found that the budget solvency of regencies and municipalities in West Nusa Tenggara Province shows relatively good outcomes and exceeds the financial health indicators for local government budget solvency.